2014
DOI: 10.4028/www.scientific.net/amr.936.728
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Anti-Tumor Activity of Polysaccharides from <i>Phellinus pini</i> Mycelia

Abstract: Polysaccharides PSIand PSIIwere isolated from liquid-cultured mycelia of Phellinus pini. The average molecular weight: PSI36 kDa, PSII49 kDa; sulfate content: PSI5.25%, PSII0.65%; monosaccharide composition: PSIglucose, galactose and mannitose; PSIIglucose, mannitose and xylose. Anti-tumor activities of PSIand PSII(400 mg/kg·d, i.g.) were investigated in S180-bearing mice. Results indicated that PSIand PSIIsignificantly inhibited the growth of S180-solid tumors. PSIand PSIIeffectively protected immune organs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…P. pini and P. igniarius are members of Phellinus species have been reported as medicinal mushrooms in China, Japan, and Korea (Ajith & Janardhanan, ). In recent years, numerous studies have demonstrated that polysaccharides isolated from P. pini and P. igniarius displayed antioxidant and antitumor activities (Jiang, Yuan, Cai, Jiao, & Zhang, ; Li, Yang, Ma, Yan, & Guo, ; Liu et al, ; Yuan et al, ). G. adspersum , G. lucidum, and G. applanatum belongs to Ganoderma species, which is considered as an important source of bioactive compounds in worldwide (Ferreira et al, ; Tel‐Çayan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…P. pini and P. igniarius are members of Phellinus species have been reported as medicinal mushrooms in China, Japan, and Korea (Ajith & Janardhanan, ). In recent years, numerous studies have demonstrated that polysaccharides isolated from P. pini and P. igniarius displayed antioxidant and antitumor activities (Jiang, Yuan, Cai, Jiao, & Zhang, ; Li, Yang, Ma, Yan, & Guo, ; Liu et al, ; Yuan et al, ). G. adspersum , G. lucidum, and G. applanatum belongs to Ganoderma species, which is considered as an important source of bioactive compounds in worldwide (Ferreira et al, ; Tel‐Çayan et al, ).…”
Section: Introductionmentioning
confidence: 99%